An exploratory study on predictors associated with teachers’ job satisfaction in Malaysian sports schools - Azizi Yahaya; Ismail Maakip; Voo, Peter Su Kiong; Kwan, Sharon Sam Mee; Balan Rathakrishnan; Sonny Jumpo (Niu jin da xue zhu ban she, 2021)
Job satisfaction is one of the hottest topics among the working population, including those in the teaching profession. However, a lack of study has been undertaken to examine predictors associated with teachers' job satisfaction in boarding schools in Malaysia. Given this, the present study aimed to investigate predictors of teachers' job satisfaction: school discipline climate, management style, and friendship quality. This cross-sectional study involved 105 teachers from two Malaysian Sports Schools. Four instruments were utilized: The School Discipline Climate Survey (SDCS) for measuring the aspect of school discipline climate, Leader Behavior Description Questionnaire (LBDQ) for examining management style, Friendship Quality Scale (FQS) was to assess factors of friendship quality, and Job Satisfaction Questionnaire to measure job satisfaction. Predictors associated with job satisfaction among teachers in sports school in Malaysia were discipline teamwork (M = 4.11, SD = 0.54), the directive style (M = 3.63, SD = 0.38) and closeness (M = 4.08, SD = 0.44). The study also found that management style was significantly correlated to job satisfaction (r = 2.12, p < 0.05). In addition, there was a difference in gender for management style (t = 2.32, p < 0.05). The study findings contributed to the knowledge of predictors associated with job satisfaction among those in the teaching profession in Malaysia and highlighted the importance of predictors that need to be taken into account with regards to job satisfaction among teachers and in developing appropriate strategies in maximizing job satisfaction at the workplace. Numerous predictors associated with boarding school (i.e., those in sports school) teachers' job satisfaction may differ from other teaching professions, such as primary and secondary school. Thus, improving and understanding the influence of school discipline climate, management style, and friendship quality towards teacher's job satisfaction with regards to enhancing satisfaction among teachers.